Cytotoxic T-Lymphotyces antigen 4 gene polymorphism and cytokine levels among severe haemophilia a patients with and without inhibitors - Nadarajan, Anantha Kummar (2020)
Introduction: Haemophilia A (HA) is an inherited X-chromosome recessive disorder characterized by factor VIII (FVIII) deficiency. High risk of spontaneous bleeding is present among patients with severe HA (FVIII < 1%). FVIII concentrate infusion is the preferred treatment for patients with severe HA however, the formation of neutralizing antibodies known as inhibitor is one of the most significant complications. The neutralizing antibodies inhibits the coagulation activity against the infused concentrated FVIII. The aim of this study is to characterize the gene polymorphism encoding for -49 (A/G) and -318 (C/T) alleles of Cytotoxic T-Lymphocytes Antigen 4 (CTLA-4) which relate to the inhibitors development. Cytokines level of interleukin 4 (IL4), interleukin 10 (IL10) and tumor necrosis factor alpha (TNFα) were measured to link with inhibitors development. Materials/Methodology: Whole blood and DNA of 64 severe HA respondents with and without inhibitor collected from PDN were analysed for gene polymorphisms using the Polymerase Chain Reaction Restriction Fragment Length Polymorphism (PCR-RFLP) and cytokines level were measured using the Enzyme-linked Immunosorbent Assay (ELISA). Data were analyzed using Statistical Package for the Social Sciences (SPSS) version 23.0. Results: There were 32 respondents with inhibitors and 32 respondents without inhibitors. Among the respondents, almost half (46.9%) of which had high titre inhibitors (≥5 BU) and another half of the respondents (53.1 %) had low titre inhibitors. Cytokines measurement expressed mixed pattern among respondents. Higher expression of IL4 was noted in repondents with inhibitors especially those with inhibitors of ≥5 BU/ml but this was statistically not significant. Statistical comparison of CTLA-4 -49 (A/G) polymorphisms with IL4 showed homozygous G/G genotypes patients with inhibitors had higher level of IL4 concentration but statistically not significant. Patients with inhibitors titre of ≥ 5 BU/ml expressed higher level of IL10 concentration but TNFα concentration was expressed at a lower level. These findings were statistically significant (p<0.05). Discussion/Conclusion: This study found gene polymorphisms of CTLA-4 -49 (A/G) and CTLA-4 -318 (C/T) were not significantly different among severe HA with inhibitors and without inhibitors. However, the findings of the mixed pattern of cytokine profiles of IL4, TNFα and IL10 in severe haemophilia A patients seemed to be associated with the presence of FVIII inhibitors which requires further verification with a study using a larger sample size.